2000
DOI: 10.1046/j.1365-2362.2000.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of OX40 in immunologically mediated diseases of the gastrointestinal tract (celiac disease, Crohn's disease, ulcerative colitis)

Abstract: OX40 is highly expressed in the gastrointestinal tissue of patients with immunologically mediated bowel diseases. Together with previous studies in animal models for these diseases, the present results point to a potential role of OX40 in their pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 22 publications
(12 reference statements)
4
27
0
Order By: Relevance
“…Furthermore, a strong downregulation by probiotic strains of T h 1 cytokines, such as IL-2, IFN-c and the proinflammatory IL-17, has been reported in other studies using different model systems (Lee et al 2009;Llopis et al 2009;Reiff et al 2009;Schultz et al 2002). Two other genes relevant to IBD that followed this pattern were TNFRSF9 (also referred to as 4-1BB) and TNFRSF4 (Ox-40) (Lee et al 2005;Stuber et al 2000;Totsuka et al 2003). They are members of the tumor necrosis factor receptor (TNFR) family that sustain T cell numbers and responses after initial CD28-dependent T cell activation (Croft 2009).…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, a strong downregulation by probiotic strains of T h 1 cytokines, such as IL-2, IFN-c and the proinflammatory IL-17, has been reported in other studies using different model systems (Lee et al 2009;Llopis et al 2009;Reiff et al 2009;Schultz et al 2002). Two other genes relevant to IBD that followed this pattern were TNFRSF9 (also referred to as 4-1BB) and TNFRSF4 (Ox-40) (Lee et al 2005;Stuber et al 2000;Totsuka et al 2003). They are members of the tumor necrosis factor receptor (TNFR) family that sustain T cell numbers and responses after initial CD28-dependent T cell activation (Croft 2009).…”
Section: Discussionsupporting
confidence: 55%
“…Bansal-Pakala et al (41) recently reported that OX40 crosslinking can provoke Ag-specific proliferation and cytokine production by CD4 ϩ T cells that are anergic in the absence of the OX40 signal, indicating that OX40 signaling can overcome CD4 ϩ T cell tolerance. Consistent with this, the expression of OX40 and/or OX40L has been demonstrated in the tissues of several immune disorders in humans such as graft-vs-host disease (42), proliferative lupus nephritis (43), rheumatoid arthritis (44), human inflammatory bowel disease (IBD) (45,46), and human inflammatory muscle diseases (47), and in thymomas of patients with myasthenia gravis (48). Despite these suggestive observations, a clear link between the OX40-OX40L interaction and the development of these immune disorder-associated diseases remains to be established.…”
Section: Cells That Have Been Described Cd25mentioning
confidence: 60%
“…OX40 has been reported to be expressed on autoreactive or effector T cells in patients with autoimmune diseases (34,36,40) and inflammatory diseases linked to immune disorders (37)(38)(39). The OX40/OX40L system may thus play a potential key role in the immune regulation of various autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OX40 stimulation has been reported to prevent peripheral tolerance of CD4 ϩ T cells (25), suggesting a possible involvement of the OX40/OX40L system in regulating autoimmunity. Indeed, expression of OX40 and/or OX40L has been demonstrated in the tissues of several immune disorders such as experimental allergic encephalitis (24, 26 -28), experimental inflammatory bowel diseases (IBDs) (29,30), graft-vs-host disease (31)(32)(33), human proliferative lupus nephritis (34), rheumatoid arthritis (35,36), human IBD (37,38), human inflammatory muscle diseases (39), and in thymoma of patients with myasthenia gravis (40). In vivo blockade of OX40/ OX40L interaction has been described not only to suppress ongoing experimental allergic encephalitis (28) and graft-vs-host disease (32,41), but also to ameliorate ongoing colitis in murine models of IBD (29,30), asthma (42), and collagen-induced arthritis (35).…”
mentioning
confidence: 99%